Application of Digital Literacy Using Mapalus Techniques in Learning in North Sulawesi - Rahmania Rahman; Paulus Tuerah; Sangputri Sidik; Hilda V. Oroh (Technium Education and Humanities, 2024)
Entering the era of the fourth world industrial revolution in this case information technology has become the basis of human life. In this era almost all life effects utilize digital, including in learning, one of which is digital literacy. Along with technological advances and the increasing individualism of society due to globalization, for this reason this study collaborates digital literacy and local culture, namely mapalus which means cooperation in learning in North Sulawesi. The purpose of the study is to determine the process of implementing digital literacy with the mapalus technique and to evaluate the effects of implementing digital literacy with the mapalus technique in learning. This research is a descriptive qualitative type of research. The data collection techniques used are observation, interviews and documentation. The results of the study show that the application of digital literacy in learning facilitates easy access for students to materials and assignments given by educators. This also increases students’ interest in using technology in the learning process and by using the malapus technique which makes students work together and work together to complete the tasks given in learning.